Structure and phase formation behavior and dielectric and magnetic properties of lead iron tantalate-lead zirconate titanate multiferroic ceramics. (March 2016) - Wongmaneerung, R.; Tipakontitikul, R.; Jantaratana, P.; Bootchanont, A.; Jutimoosik, J.; Yimnirun, R.; Ananta, S.
Graphical abstract: Highlights: The multiferroic ceramics consisted of PFT and PZT. Crystal structure changed from cubic to mixedcubic and tetragonal with increasing PZT content. Dielectric showed the samples underwent a typical relaxor ferroelectric behavior. Magnetic properties showed very interesting behavior with square saturated magnetic hysteresis loops. Abstract: Multiferroic (1 − x )Pb(Fe0.5 Ta0.5 )O3 – x Pb(Zr0.53 Ti0.47 )O3 (or PFT–PZT) ceramics were synthesized by solid-state reaction method. The crystal structure and phase formation of the ceramics were examined by X-ray diffraction (XRD). The local structure surrounding Fe and Ti absorbing atoms was investigated by synchrotron X-ray Absorption Near-Edge Structure (XANES) measurement. Dielectric properties were studied as a function of frequency and temperature using a LCR meter. A vibrating sample magnetometer (VSM) was used to determine the magnetic hysteresis loops. XRD study indicated that the crystal structure of the sample changed from pure cubic to mixed cubic and tetragonal with increasing PZT content. XANES measurements showed that the local structure surrounding Fe and Ti ions was similar. Dielectric study showed that the samples underwent a typical relaxor ferroelectric behavior while the magnetic properties showed very interesting behavior with square saturated magnetic hysteresis loops.